2017
DOI: 10.1073/pnas.1618514114
|View full text |Cite
|
Sign up to set email alerts
|

Splicing variation of Long-IRBIT determines the target selectivity of IRBIT family proteins

Abstract: IRBIT [inositol 1,4,5-trisphosphate receptor (IP 3 R) binding protein released with inositol 1,4,5-trisphosphate (IP 3 )] is a multifunctional protein that regulates several target molecules such as ion channels, transporters, polyadenylation complex, and kinases. Through its interaction with multiple targets, IRBIT contributes to calcium signaling, electrolyte transport, mRNA processing, cell cycle, and neuronal function. However, the regulatory mechanism of IRBIT binding to particular targets is poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…However, given that authentic L-IRBIT (L-IRBIT V1 or L-IRBIT V2) was predominantly expressed in B16-F10 cells, and that L-IRBIT KO cells were produced using a guide RNA sequence that targets a common exon of all L-IRBIT variants, our results likely reflect the effects of IRBIT and authentic L-IRIBT. However, as shown in a previous report 12 , short variants of L-IRBIT show a more marked cell type-specific expression. Thus, especially in some cell types, the contribution of short-form L-IRBIT variants to AE2 regulation should be verified in future studies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, given that authentic L-IRBIT (L-IRBIT V1 or L-IRBIT V2) was predominantly expressed in B16-F10 cells, and that L-IRBIT KO cells were produced using a guide RNA sequence that targets a common exon of all L-IRBIT variants, our results likely reflect the effects of IRBIT and authentic L-IRIBT. However, as shown in a previous report 12 , short variants of L-IRBIT show a more marked cell type-specific expression. Thus, especially in some cell types, the contribution of short-form L-IRBIT variants to AE2 regulation should be verified in future studies.…”
Section: Discussionsupporting
confidence: 73%
“…At the cellular level, however, L-IRBIT shows a more restricted expression pattern than IRBIT, for example, the specific expression in some interneurons of the cerebellum 9 . A recent report of splicing variants of L-IRBIT with different N-terminal sequences has shown that each variant has unique properties in protein stability, target molecule spectrum, and functional consequence 12 . Together, IRBIT and L-IRBIT can form homo-or hetero-multimers via conserved AHCY domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed an expression vector encoding human IP 3 R1 (SI − /SII + /SIII − splicing variant) (33) with an N-terminal mRFP-P2A tag. The peptide bond at the C terminus of the P2A peptide is cleaved in cells, and mRFP fluorescence can be used as a marker of transfected cells (36). We generated 14 missense mutants of human IP 3 R1: R241K, T267M, T267R, R269G, R269W, S277I, K279E, A280D, V479I, E497K, T579I, N587D, S1478D, and V1538M, identified in SCA29, SCA15, and ataxic cerebral palsy (2-10, 13, 32) ( Fig.…”
Section: Significancementioning
confidence: 99%
“…IRBIT was discovered as a molecule that binds to the IP 3 -binding pocket of IP 3 R [146,147]. In contrast, an IRBIT homologue Long-IRBIT does not interacts with IP 3 R1 because its long N-terminal appendage inhibits the interaction [148,149]. IRBIT is a multifunctional protein that regulates diverse proteins including Na + -HCO 3 co-transporter, CFTR, Na + -H + exchanger [150], CaM kinase IIα [151], and PIP kinases [152].…”
Section: Irbit a New Sensor For The Environment Interaction: Novel Omentioning
confidence: 99%